Inclusive landscape management plan for resilient agri-food system in the Nyamagana landscape in Burundi - Niyuhire, M. C.; Atampugre, Gerald; Tilahun, Seifu A.; Cofie, Olufunke O.; Havyarimana, D.; Niyoyankunze, J. M. V. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2024)
The Inclusive Landscape Management (ILM) is a comprehensive approach to landscape management that considers the needs of all stakeholders, with particular focus on the local communities. The primary aim of the Inclusive Landscape Management Plan (ILMP) for Cibitoke Province in Burundi is to establish a framework that promotes sustainable landscape management and development. This initiative, part of the TAFS-WCA project, seeks to mitigate increasing pressures on landscapes caused by deforestation, land degradation, poor water management, unsustainable mining practices, and climate change.